HEAVY METALS CONCENTRATIONS IN RAW COW MILK PRODUCED IN THE DIFFERENT LIVESTOCK FARMING TYPES IN GUELMA PROVINCE ( AL GERIA) : CONTAMINATION AND RISK ASSESSMENT OF CONSUMPTION - A. Bousbia; S. Boudalia; Y. Gueroui; R. Ghebache; M. Amrouchi; B. Belase; S. Meguelati; B. Belkheir; M. Benidir; M. L. Chelaghmia (Journal of Animal and Plant Sciences, 2019)
In the present study, we investigated the potential sources of environmental milk contamination; by evaluating heavy metals concentration, and the assessment of human health risks related to milk consumption in the region of Guelma, Algeria. A total of forty-eight random livestock farming (extensive, intensive and peri-urban) were selected, and a survey protocol was used to collect data on polluted environment using questionnaires, then the pollution risk indicators were calculated. From this livestock farming, 144 milk samples were collected and then mineralized; quantitative analysis of Fe, Cu, Zn, Cd, and Cr was performed using an atomic absorption spectrophotometer. Finally, for each element, the estimated daily intake (EDI) was calculated. The comparison of the synthetic pollution index according to the different types of livestock farming, revealed a significant difference between low values for extensive livestock farming and high values for peri-urban livestock farming. From the analytic analysis, the results indicated that the average milk concentrations of Fe, Cu, Zn, and Cd were higher than the suggested standards. The EDI values for Cd, Zn and Cr were higher compared to permissible values. To examine the possible effects of milk consumption on human health, further investigations of the levels of heavy metals in a greater number of milk samples from various zones are necessary.
Keywords: Cow; milk; heavy metals; livestock farming; pollution; estimated daily intake (EDI)